Potrebnost ali škodljivost vpletanja politike v razvoj gozdarstva - Falkner, Jože (Gozdarski vestnik, 2009)
The article deals with the interventions of the politics in the Slovenian Forestry in the last 20 years. It presents positive and negative experiences.
Keywords: forestry; gozdarstvo; politics; politika; državni gozdovi; zasebni gozdovi; Slovenia; Slovenija